2005
DOI: 10.1002/jts.20055
|View full text |Cite
|
Sign up to set email alerts
|

Psychological consequences of the Bam earthquake on professional and nonprofessional helpers

Abstract: This study compared the psychological status of rescue personnel who had formal training (Red Crescent workers, i.e., Red Cross workers, and firefighters) with university student volunteers who had no formal training in handling traumatic situations in the Bam earthquake. One hundred student volunteers, 18 Red Crescent workers, and 36 firefighters participated in this study. Participants completed the Civilian Mississippi Scale, the General Health Questionnaire (GHQ-28), and the Anxiety Sensitivity Index. Help… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
56
2
5

Year Published

2007
2007
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(66 citation statements)
references
References 25 publications
1
56
2
5
Order By: Relevance
“…This possibility is consistent with pervious studies reporting higher levels of PTSD symptoms among non-professional rescue workers compared to professional ones. [18,19] Another possible moderator of the association between exposure to stress and PTSD in this study was gender. The higher level of PS and probable PTSD in female participants in this study is consistent with previous reports of women being more likely than men to experience PTSD symptoms.…”
Section: Discussionmentioning
confidence: 95%
“…This possibility is consistent with pervious studies reporting higher levels of PTSD symptoms among non-professional rescue workers compared to professional ones. [18,19] Another possible moderator of the association between exposure to stress and PTSD in this study was gender. The higher level of PS and probable PTSD in female participants in this study is consistent with previous reports of women being more likely than men to experience PTSD symptoms.…”
Section: Discussionmentioning
confidence: 95%
“…These individual were thought to be protected by their commitment to a cause, training in stoicism, and prior knowledge about torture techniques [Basoglu et al, 1997]. Other researchers have also found that prior training in emergency work appears to enhance resilience [Alvarez and Hunt, 2005;Hagh-Shenas et al, 2005].…”
Section: Psychological Resilience To Ptsdmentioning
confidence: 92%
“…Several studies have documented positive correlations between AS and posttraumatic stress symptom levels among traumatic event exposed adults (e.g., Feldner, Zvolensky, Schmidt, & Smith, in press;Hagh-Shenas, Goodarzi, Dehbozorgi, & Farashbandi, 2005). Asmundson, Norton, Allerdings, Norton, and Larsen (1998) examined AS and posttraumatic stress among 121 adults who had experienced a work-related injury.…”
mentioning
confidence: 99%